Applying large groups interaction methods in the planning and implementation of major change efforts - Bryson, John M.; Anderson, Sharon R. (2000)
Public policy makers, planners, and managers are increasingly relying on what might be called large-group interaction methods to involve large numbers of people (from as few as eight to more than 2,000) in planning and implementing major change efforts. These methods are structured processes for engaging large numbers of people to: (1) enhance the amount of relevant information brought to bear on a problem; (2) build commitment to problem definitions and solutions; (3) fuse planning and implementation; and (4) shorten the amount of time needed to conceive and execute major policies, programs, services, or projects. Proponents of such methods claim that they provide sets of concepts, procedures, and tools that can help public and nonprofit organizations and communities deal effectively with change. On the other hand, a number of boundary conditions surround the successful use of the methods. The authors compare and contrast seven approaches most frequently used in the public sector in the United States and abroad (i.e., Real Time Strategic Change, Search Conferences, Future Searches, Strategic Options Development and Analysis, Strategic Choice, Technology of Participation, and Open Space Technology) to illustrate their comparative strengths and weaknesses and to develop an agenda for research. - Reproduced
Keywords: Public policy